Reactive Gelation Synthesis of Monodisperse Polymeric Capsules Using Droplet‐Based Microfluidics. Issue 6 (17th May 2019) - Yang, Tianjin; Cingolani, Alberto; Casalini, Tommaso; Aribia, Abdessalem; Klaue, Antoine; Wu, Hua; Stavrakis, Stavros; de Mello, Andrew; Morbidelli, Massimo
Abstract: A novel methodology, combining reactive gelation and droplet‐based microfluidics, is described for the synthesis of rigid, porous, and hollow polymeric nanoparticles (NPs). The precursors of such capsules are microfluidically generated latex droplets, with diameters tunable between 20 and 100 µm. The conversion of latex droplets to polymeric capsules involves two steps, namely self‐migration and gelation of the NPs toward the oil–water interface to form a solid‐like shell, and then postpolymerization to covalently fix the shell structure. The hollow structure of the capsules results from the interaction between negatively charged NPs inside the droplet and positive charges present on fluorosurfactant at the droplet interface. Significantly, the porosity and average pore size in the capsule shell can be controlled through variation of the initial NP concentration in the droplet. Based on the analysis of diffusion of fluorescent molecules of known size, it is shown that penetration of molecules into the internal volume of the capsules increases as the initial NP concentration in the droplet decreases, thus the porosity of the formed shell increases. This novel synthetic methodology defines a powerful tool in the generation of hollow capsules of controlled size and morphology, and has significant application in material sciences. Abstract : A novel methodology, combining reactive gelation and droplet‐based microfluidics, for the synthesis of rigid, porous, and hollow polymeric particles is reported. This novel synthetic methodology defines a powerful tool in the generation of hollow capsules of controlled size and morphology, and has significant application to a wide variety of processes in the pharmaceutical and material sciences.